2018
DOI: 10.1177/0004867417750756
|View full text |Cite
|
Sign up to set email alerts
|

Patient predictors of response to cognitive behaviour therapy and schema therapy for depression

Abstract: Study findings are consistent with the Capitalisation Model suggesting that therapy that focuses on the person's strengths is more likely to contribute to a better outcome. Limitations were that participants were outpatients in a randomised controlled trial and may not be representative of other depressed samples. Examination of a variety of potential predictors was exploratory and requires replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…To our knowledge, fewer than 10 RCTs have evaluated the effectiveness of individual and/or group schema therapy. RCTs have been conducted with individuals with BPD (Arntz et al, 2022; Farrell et al, 2009; Giesen‐Bloo et al, 2006; Leppänen et al, 2016), personality disorders (Bamelis et al, 2014), binge eating problems (McIntosh et al, 2016), depression (Carter et al, 2018; Porter et al, 2016) and criminal histories (Bernstein et al, 2021). Although the evidence regarding effectiveness based on RCTs is strongest for BPD, well‐designed effectiveness studies across the areas outlined by the panel are needed to improve confidence in expanding the clinical application of the schema therapy model.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, fewer than 10 RCTs have evaluated the effectiveness of individual and/or group schema therapy. RCTs have been conducted with individuals with BPD (Arntz et al, 2022; Farrell et al, 2009; Giesen‐Bloo et al, 2006; Leppänen et al, 2016), personality disorders (Bamelis et al, 2014), binge eating problems (McIntosh et al, 2016), depression (Carter et al, 2018; Porter et al, 2016) and criminal histories (Bernstein et al, 2021). Although the evidence regarding effectiveness based on RCTs is strongest for BPD, well‐designed effectiveness studies across the areas outlined by the panel are needed to improve confidence in expanding the clinical application of the schema therapy model.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Schema Therapy on psychological health has been documented. There is strong support from randomized clinical trials examining the efficacy of Schema Therapy for depression (Carter et al, 2018; Renner et al, 2013), anxiety (Peeters et al, 2021), and improving psychological well-being (Mohammad Nezhady & Rabiei, 2015) on clients with a history of interpersonal trauma. A study by Renner et al (2016), found that compared to the no-treatment control group, the intervention group had a significant large effect on depressive symptoms.…”
Section: Cultural Contextmentioning
confidence: 99%
“…Cognitive impairment plays a key role as a transdiagnostic factor in psychiatric disorders in general and MDD in particular [ 146 148 ]. These deficits affect different cognitive domains such as memory, executive functions, attention, and learning [ 149 , 150 ] and in many cases outlast the remission of depressive symptoms [ 151 , 152 ].…”
Section: Measures and Hypothesesmentioning
confidence: 99%